Analysis of Environmental Litercy Skills Among Junior High School and Islamic Junior Hihg School Students in Adiwiyata and Non-Adiwiyata Schools in Batu City - Azza, Rinata Aqila; Husamah, H.; Rahardjanto, Abdulkadir (Jurnal Report of Biological Education, 2025)
Background: Environmental literacy is an important and interesting issue to explore considering the lack of literature discussing this issue.This study aims to analyze the environmental literacy skills of junior high school (SMP) and Islamic junior high school (MTs) students in Batu city. A descriptive quantitative approach was used, with data collected through a google-form-based questionare completed by 1,291 students from six purposively selected schools. The independent variabels in this study are school status (Adiwiyata and non-Adiwiyata) and students gender, while the dependent variabel is environmental literacy skills. Data were analyzed using descriptive statistics, a normality test, and the non-parametric Mann-Whitney test. The results show taht, in general students environmental literacy levels fall into the “very high” category, with an average score of 112.69. There are significant differences in environmental literacy skills based on school type and gender. Female students tend to have higher environmental literacy scores than male students and non-Adiwiyata schools showed slightly higher scores compared to Adiwiyata schools. The findings indicate that both schools type and gender have an influence on students environmental literacy outcomes, and the responses provided by the students are generally categorized as “Excellent”.